2014
DOI: 10.1017/s1368980014000767
|View full text |Cite
|
Sign up to set email alerts
|

Diet quality among Iranian adolescents needs improvement

Abstract: Objective: Diet in adolescence is important not only because of adolescents' rapid growth but also due to its influence on future chronic diseases. On the other hand, dietary quality indices are noteworthy and useful approaches to evaluate dietary intakes. Thus the present study was conducted to assess dietary quality indices in adolescents. Design: Cross-sectional. Settings: The data were collected from schools in Isfahan, Iran. Subjects: Female students (n 265) aged 11-13 years were enrolled using systematic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
64
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 60 publications
(72 citation statements)
references
References 31 publications
4
64
2
Order By: Relevance
“…To conclude, the findings of the present study emphasise the importance of high intakes of nuts and soy and fruits in the reduction of 10‐year CVD risk. The present study is consistent with previous research showing that the diet quality of many Iranians may need to be improved through nutrition education and other public health interventions, as appropriate .…”
Section: Discussionsupporting
confidence: 92%
“…To conclude, the findings of the present study emphasise the importance of high intakes of nuts and soy and fruits in the reduction of 10‐year CVD risk. The present study is consistent with previous research showing that the diet quality of many Iranians may need to be improved through nutrition education and other public health interventions, as appropriate .…”
Section: Discussionsupporting
confidence: 92%
“…Although there are some reports regarding the dietary intakes of patients with NAFLD, according to the best of our knowledge, there is no report on the quality of diet and whole diet indices among these patients. Previous studies among Iranian population showed that HEI could be a good indicator for evaluating dietary quality in this population (42, 43). Those subjects who have higher score of HEI, usually may intake higher fruit and vegetable and lower unsuitable fat.…”
Section: Discussionmentioning
confidence: 94%
“…To the best of our knowledge, few studies have evaluated the association of the DQI‐I and HEI‐2010 separately with CVD risk factors in the Iranian population . No studies exist concerning the association of the DQI‐I and HEI‐2010 with CVD risk factors among diabetic patients.…”
Section: Introductionmentioning
confidence: 99%